2020
DOI: 10.1002/ijc.33381
|View full text |Cite
|
Sign up to set email alerts
|

Tie2‐expressing monocytes as a novel angiogenesis‐related cellular biomarker for non‐small cell lung cancer

Abstract: To investigate the clinical value of Tie2‐expressing monocytes (TEMs) in the early diagnosis of lung cancer and assess its correlation with angiogenesis, a total of 184 patients with non‐small cell lung cancer (NSCLC), 101 patients with benign pulmonary disease (BPD), and 77 healthy controls were enrolled in our study. The distribution of TEMs in lung tissue was determined by immunofluorescence staining. Lung microvascular density was assessed by immunohistochemical staining. Receiver‐operating characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Consistently with these results, the proportion of TEMs amongst total tissue TAMs is correlated with total tumor microvascular density in human ovarian, renal cell carcinoma, hepatocellular carcinoma, and non-small cell lung cancer, but not in colorectal cancer [29,102,170,171]. High TEM infiltration or high number of circulating TEMs is correlated with poor prognosis in ovarian cancer and in hepatocellular carcinoma, respectively, whereas it is surprisingly correlated with good prognosis in hilar cholangiocarcinoma [102,[172][173][174][175]. These TEMs are also found in hypoxic and tumor areas enriched in small immature non-pericytic blood vessels [123,176].…”
Section: )supporting
confidence: 64%
“…Consistently with these results, the proportion of TEMs amongst total tissue TAMs is correlated with total tumor microvascular density in human ovarian, renal cell carcinoma, hepatocellular carcinoma, and non-small cell lung cancer, but not in colorectal cancer [29,102,170,171]. High TEM infiltration or high number of circulating TEMs is correlated with poor prognosis in ovarian cancer and in hepatocellular carcinoma, respectively, whereas it is surprisingly correlated with good prognosis in hilar cholangiocarcinoma [102,[172][173][174][175]. These TEMs are also found in hypoxic and tumor areas enriched in small immature non-pericytic blood vessels [123,176].…”
Section: )supporting
confidence: 64%
“…Tie2 expression was almost undetected on CD16-negative monocytes [ 5 ]. Likewise, consistent with our study, Xue et al [ 26 ] revealed that Tie2 was mainly expressed in CD14 + CD16 + cells rather than in CD14 + CD16 − cells.…”
Section: Discussionsupporting
confidence: 93%
“…TEM frequency showed a correlation with NSCLC (non-small cell lung cancer) recurrence. The high percentage of TEMs in the peripheral blood was associated with a lower survival rate [ 26 ]. Likewise, the interactions between CLL cells and their microenvironment in bone marrow, lymph nodes and peripheral blood are believed to have a significant impact on the pathophysiology of the disease [ 14 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the Ang1-Tie2 axis promotes vessel maturation and vascular integrity, while Tie2 axis causes vessel neovascularization and regression; this type of monocyte is known as Tie2 expressing monocytes (TEMs) and is linked to the creation of tumour vessels. TEMs have been proven in preclinical investigations to enhance tissue remodelling, and tumour angiogenesis (11) .…”
Section: Discussionmentioning
confidence: 99%